2012
DOI: 10.1088/0004-637x/762/1/20
|View full text |Cite
|
Sign up to set email alerts
|

On the Hot Gas Content of the Milky Way Halo

Abstract: The Milky Way appears to be missing baryons, as the observed mass in stars and gas is well below the cosmic mean. One possibility is that a substantial fraction of the Galaxy's baryons are embedded within an extended, million-degree hot halo, an idea supported indirectly by observations of warm gas clouds in the halo and gas-free dwarf spheroidal satellites. X-ray observations have established that hot gas does exist in our Galaxy beyond the local hot bubble; however, it may be distributed in a hot disk config… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
133
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 71 publications
21
133
2
Order By: Relevance
“…Thus, the halo has a global baryon fraction of 0.16, consistent with the cosmic value of f b = Ω b /Ωm. Some of the recent observations have revealed that the baryon fraction can be ∼ 0.1 for massive spirals (Bogdan et al 2013), and in our MW, this fraction can be ∼ 0.16 for a gas with polytropic index γ = 5/3 in hydrostatic equilibrium (Fang et al 2013;Gatto et al 2013). Though here we assume f b = 0.16, we have also checked the effect of f b on the mass loading factor at virial radius (see §4.3).…”
Section: Setting the Initial Density Distributionsupporting
confidence: 55%
“…Thus, the halo has a global baryon fraction of 0.16, consistent with the cosmic value of f b = Ω b /Ωm. Some of the recent observations have revealed that the baryon fraction can be ∼ 0.1 for massive spirals (Bogdan et al 2013), and in our MW, this fraction can be ∼ 0.16 for a gas with polytropic index γ = 5/3 in hydrostatic equilibrium (Fang et al 2013;Gatto et al 2013). Though here we assume f b = 0.16, we have also checked the effect of f b on the mass loading factor at virial radius (see §4.3).…”
Section: Setting the Initial Density Distributionsupporting
confidence: 55%
“…However, larger samples of absorption lines (∼40 sight lines; Bregman & LloydDavies 2007;Gupta et al 2012;Fang et al 2015) and the all-sky emission-line intensities (≈1000 sight lines Henley & Shelton 2012;Miller & Bregman 2013) favor a spherical model. Similar analyses on independent observables that also probe the hot gas, such as the pulsar dispersion measure toward the Large Magellanic Cloud and the ram-pressure stripping of Milky Way satellites favor an extended halo (Fang et al 2013;Salem et al 2015). Finally, a recent analysis of both Galactic and extragalactic sightlines for L * galaxies finds that the O VII traces hot gas (Faerman et al 2016).…”
Section: Halo and Disk Modelsmentioning
confidence: 95%
“…First, the baryon fraction that can collapse into low mass halos is strongly reduced (Mo & Mao 2002;van den Bosch, Abel & Hernquist 2003;Oh & Benson 2003;McCarthy et al 2004;Scannapieco & Oh 2004;Lu & Mo 2007). Second, when the entropy of the pre-collapsed gas is higher than would be generated by accretion shocks, the halo gas is expected to develop an extended density distribution (Mo & Miralda-Escude 1996;Mo & Mao 2002;Maller & Bullock 2004;Kaufmann et al 2009;Fang, Bullock & Boylan-Kolchin 2013), thereby affecting where and when halo gas cools to fuel the central disk. Using a semi-analytic model built upon simulated halo accretion histories, we examine in detail the disk size evolution, mass assembly and star formation histories of central galaxies hosted by halos with masses Mvir < 10 12 M⊙ at the present time in the preheating scenario.…”
Section: Introductionmentioning
confidence: 99%